Proximal radial pseudotumour: Magnetic resonance imaging appearances and prevalence - Ian Pressney Michael Khoo; Asif Saifuddin (Annals of Bone Marrow Research - Peertechz Publications, 2020)
Introduction: Cases have been referred to our tertiary referral sarcoma service where marrow abnormalities have been identified in the proximal radius. We believe this to be a normal variant, likely representing residual red marrow. The purpose of this study is to describe the features and determine the prevalence of such a finding on elbow magnetic resonance imaging (MRI) in an unselected group of patients imaged at our institution.  Materials and methods: Retrospective review of the last 100 elbow MRI studies performed at our institution. Patient age, sex, side imaged and reason for MRI were recorded.  The proximal radial pseudotumour, was defined as a region of marrow signal abnormality with intermediate T1W SE/ T2W FSE/PDW FSE signal intensity between medullary fat and skeletal muscle with hyperintense STIR/PDW FS signal compared to medullary fat, but hypointense to joint fluid. For positive cases, the length and distance from the proximal radial articular surface was measured. Also, local changes, including cortical abnormality, active periostitis, surrounding soft tissue abnormality and similar change in distal humerus and proximal ulna were assessed.  Results: The pseudotumour was identified in 7.8% of cases. No statistical differences were observed for age (p=0.1), laterality (p=0.08) or sex (p=0.79) for pseudotumour presence. Mean length of pseudotumour was 21 mm with mean distance from the articular surface of 16 mm.  Conclusions: The proximal radial pseudotumour is seen in 7.8% of elbow MRI studies and should be recognised as a normal variant of proximal radial marrow signal intensity.